2016
DOI: 10.1063/1.4962968
|View full text |Cite
|
Sign up to set email alerts
|

Development of an advanced microfluidic micropipette aspiration device for single cell mechanics studies

Abstract: Various micro-engineered tools or platforms have been developed recently for cell mechanics studies based on acoustic, magnetic, and optical actuations. Compared with other techniques for single cell manipulations, microfluidics has the advantages with simple working principles and device implementations. In this work, we develop a multi-layer microfluidic pipette aspiration device integrated with pneumatically actuated microfluidic control valves. This configuration enables decoupling of cell trapping and asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…A variation of micropipette aspiration has recently overcome a key limitation of the technique: the relatively low throughput of the experiments ($20 cells/h). Lee et al developed a new microfluidic device based on microaspiration that has greatly increased the throughput of the technique ($1000 cells/h) (67), complementing other microfluidics approaches to measure cell-deformability parameters with a high throughput (68) (Fig. 4 g).…”
Section: New Approaches: the Need For Additional Measurementsmentioning
confidence: 99%
“…A variation of micropipette aspiration has recently overcome a key limitation of the technique: the relatively low throughput of the experiments ($20 cells/h). Lee et al developed a new microfluidic device based on microaspiration that has greatly increased the throughput of the technique ($1000 cells/h) (67), complementing other microfluidics approaches to measure cell-deformability parameters with a high throughput (68) (Fig. 4 g).…”
Section: New Approaches: the Need For Additional Measurementsmentioning
confidence: 99%
“…Lee et al. have demonstrated the stiffening of breast cancer cells (MDA_MB‐231) after introducing Taxol using MA in as shown in Fig. .…”
Section: Characterization Processesmentioning
confidence: 99%
“…(A) Fluorescence image at different stages of aspiration (B) Young's modulus. Reprinted from with permission of AIP Publishing.…”
Section: Characterization Processesmentioning
confidence: 99%
“…More importantly, in the present study, we observed that CuB changed the mechanical properties of breast cancer cells. It is well known that the cytoskeleton of cancer cells is deformed more easily than that of normal cells, enhancing their ease of migration through the bloodstream to distant tissues (Lee, Lee, Chase, Gebrezgiabhier, & Liu, 2016). Changes in the cytoskeleton affect the morphology and mechanical properties of cells (Kumar & Weaver, 2009b).…”
Section: Mechanism Of Cub-induced Changes In Mechanical Properties mentioning
confidence: 99%